A rotation based multichannel least squares lattice algorithm for adaptive nonlinear filters - Yang, B. (IEEE International Symposium on Circuits and Systems, 1993, 1993)
An efficient rotation based adaptive multichannel least squares lattice algorithm for multichannel filtering with different filter orders for each input channel is presented. It is shown that this algorithm is suited for adaptive nonlinear filtering based on Volterra and recursive polynomial system models. The new algorithm requires only orthogonal transformations offering superior numerical behavior. Its highly modular and regular structure facilitates VLSI and parallel implementations.< >